Yield response of ten varieties of sweet potato (Ipomoea batatas L.) cultivated on dryland in rainy season - Akbar Saitama; Agung Nugroho; Eko Widaryanto (Brawijaya University, 2017)
Sweet potato is a tuber commodity and one of alternative crops in Indonesia. The demand of sweet potato in Indonesia continues to increase. However, the supply of sweet potatoes for consumption estimated is 2020 in Indonesia will be deficit. Low production of sweet potato is basically due to the decrease of land area as cultivation production and also sweet potatoes have a low yield when planted in rainy season. Based on the high utilization of sweet potato make demand for this commodities continues to increase.Therefore, several strategies to increase crop yields of sweet potato needs to be done. This study aimed to elucidate various sweet potato varieties that can cultivated on dry land in the rainy season. This study was conducted from November 2016 until March 2017 using a randomized block design with treatments of ten varieties of sweet potato consisting of (V1) Papua Solossa variety, (V2) Jago variety, (V3) Kidal variety, (V4) Antin-1variety, (V5) Sari variety, (V6) Sawentar variety, (V7) Beta-2variety, (V8) Antin-2variety, (V9) Antin-3 variety, (V10) Beta-1variety. The results showed different responses of each variety.The vegetative growth was high as shown by the LAI value of 7.23 at 90 days after planting. In conclusion, the sweet potato leaves had to be prune to boost the agronomic yield. Yields of ten varieties of sweet potato crops ranged from 8.86 to 44.76 t/ha. Some varieties such as Sari, Papua Salosa and Beta-2 varieties showed high yield although they were planted in moorland conditions in the rainy season.